The Study on The Relationship Between Promotional Strategies to Freshmen Students’ Perceptions and Needs in A Higher Educational Institution in Iligan City - Guro, Princess Diamond B.; Iman, Jimm M.; Pendang, Ma. Lynflora; Madura, Rhodo Feliah; Abiol, Michael Jere’ D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study delves into the impact of promotional strategies on the perceptions and needs of freshmen students in higher education institutions. Its primary objective is to scrutinize the connection between promotional strategies, customer perception, and customer needs, with the goal of formulating precise and efficient marketing tactics. Conducted at a higher education institution in Iligan City, Philippines, the research encompasses participants from various colleges, ensuring a well-rounded sample. Employing a descriptive-correlational research design, data was gathered through an online survey questionnaire and subjected to analysis through descriptive statistics and Pearson correlataion analysis. The outcomes reveal a substantial positive correlation between promotional strategies and both customer perception and customer needs. Promotional strategies that are personalized, convenient, and sustainable are shown to enhance customer experience, customer value, and brand loyalty. This study offers valuable insights for both marketers and scholars, advocating for educational institutions to implement marketing programs with a focus on promotional strategies. Future research should explore the efficacy of promotional strategies across different contexts and diverse demographic groups to ensure all-encompassing and impactful marketing strategies. By comprehending the influence of promotional strategies on customer perception and needs, businesses and educational institutions can craft tailored marketing campaigns to attract and retain customers in today's fiercely competitive market landscape.